2016
DOI: 10.1007/s00204-016-1766-z
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up studies on genome damage in children after Chernobyl nuclear power plant accident

Abstract: As children are more susceptible to ionizing radiation than adults, each nuclear accident demands special attention and care of this vulnerable population. The Chernobyl nuclear disaster occurred in a region populated with a large number of children, but despite all efforts and expertise of nuclear specialists, it was not possible to avoid casualties. As vast regions of Ukraine, Belarus and Russia were exposed to doses of ionizing radiation, which are known to be related with different diseases, shortly after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 80 publications
0
6
0
2
Order By: Relevance
“…A. Fucic et al [35] в обзорной статье о повреждениях генома среди детей ликвидаторов аварии на Чернобыльской АЭС и потомков лиц, проживавших на загрязненной территории, описывают статистически более высокую частоту дицентрических и кольцевых хромосом, хромосомных разрывов, ацентрических фрагментов, транслокаций и микроядер, чем в контроле.…”
Section: цитогенетические и молекулярно-генетические исследования насunclassified
“…A. Fucic et al [35] в обзорной статье о повреждениях генома среди детей ликвидаторов аварии на Чернобыльской АЭС и потомков лиц, проживавших на загрязненной территории, описывают статистически более высокую частоту дицентрических и кольцевых хромосом, хромосомных разрывов, ацентрических фрагментов, транслокаций и микроядер, чем в контроле.…”
Section: цитогенетические и молекулярно-генетические исследования насunclassified
“…Investigaciones en la población infantil tras el desastre nuclear de Chernobyl concluyen que las consecuencias por sobreexposición a la radiación ionizante incluyen trastornos inmunológicos, enfermedades cardiovasculares y aumento del riesgo a neoplasias, principalmente leucemias, cáncer de mama, tiroides, piel y cerebro, debido a una mayor tasa de división celular, tejidos más blandos, órganos más contiguos, mayor susceptibilidad a factores ambientales y menor diámetro corporal (17)(18)(19)(20) .…”
Section: Radiación Ionizanteunclassified
“…Most of the civilian populations were exposed to multiple pathways over time [1,2]. Cancer, primarily thyroid cancer, has been documented among exposed cohorts [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…One major concern among Chernobyl-exposed populations, was worry over reproductive health, congenital malformations and genetic damage among offspring [ 4 , 15 , 16 , 17 , 18 , 19 , 20 ]. The anticipated excess increase in stillbirths and congenital malformations was not found in all studies of Chernobyl-exposed women and children [ 4 , 17 , 18 , 21 , 22 ]. However, a recent review concluded that genetic damage was evident in some of the exposed populations, particularly if the parents were exposed to high doses stemming from on-site exposure among liquidators or if the children continued to be exposed over many years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%